Mobile pre-hospital care in portugal and brazil: An integrative review - Cyrino, Claudia Maria Silva [UNESP]; De Almeida, Priscila Masquetto Vieira [UNESP]; Dell’Acqua, Magda Cristina Queiroz [UNESP]; Deodato, Sergio; Michelin, Nathallia Serodio [UNESP]; Castro, Meire Cristina Novelli e [UNESP] (FapUNIFESP (SciELO), 2019)
Objective: To identify the profile and themes of studies found in the literature about the context of mobile pre-hospital care in Portugal and Brazil. Method: An integrative review of five online databases was conducted in February and March 2017. Full articles in English, Spanish, and Portuguese published between 1981 and 2017 were selected for this review. Results: Of the 54 studies included, nurses were present in 81.50%; 37% were related to the characteristics of care, 22% to professionals, 20% to occupational risks, 17% to management, and 4% to health education. Conclusion: The number of articles with nurses as the main authors reached a peak in 2011. Their topics were mostly related to the analysis of care provided by the services, and the knowledge and performance of professionals working in the area of mobile pre-hospital care.
Atención móvil prehospitalaria en portugal y brasil: Revisión integrativa
Pré-hospitalar móvel em portugal e brasil: Revisão integrativa
Keywords: Ambulances; Emergency medical services; Nursing; Pre-hospital services; Review